PERAN HUKUM DALAM MEMBERIKAN PERLINDUNGAN TERHADAP PEREMPUAN DARI TINDAK KEKERASAN DI ERA GLOBALISAS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Protection towards woman from violence is our responsibility as individual, society, law enforcer and government. Woman or a group of woman can file accusation to CEDAW committee (Convention on the Elimination of all forms of discrimination Against Women), concerning heavy infringement and systematic that in self or a woman group, done by person or country of CEDAW signatory countries. Law gives protection towards woman from act violence enforceable by: woman cognizance enhanced towards right and the duty